Applying multi-purpose commercial inertial sensors for monitoring equine locomotion in equestrian training - Fercher, C.; Bartsch, J.; Kluge, S.; Schneider, F.; Liedtke, A.M.; Schleichardt, A.; Ueberschär, O. (Sensors, 2024)
Inappropriate, excessive, or overly strenuous training of sport horses can result in long-term injury, including the premature cessation of a horse`s sporting career. As a countermeasure, this study demonstrates the easy implementation of a biomechanical load monitoring system consisting of five commercial, multi-purpose inertial sensor units non-invasively attached to the horse`s distal limbs and trunk. From the data obtained, specific parameters for evaluating gait and limb loads are derived, providing the basis for objective exercise load management and successful injury prevention. Applied under routine in-the-field training conditions, our pilot study results show that tri-axial peak impact limb load increases progressively from walk to trot to canter, in analogy to stride frequency. While stance and swing phases shorten systematically with increasing riding speed across subjects, longitudinal and lateral load asymmetry are affected by gait at an individual level, revealing considerable variability between and within individual horses. This individualized, everyday approach facilitates gaining valuable insights into specific training effects and responses to changing environmental factors in competitive sport horses. It promises to be of great value in optimizing exercise management in equestrian sports to benefit animal welfare and long-term health in the future.